A Way to Reach 10% Efficiency with Carbon‐Based Electrodeposited Mixed Perovskite Solar Cells. Issue 11 (20th September 2022) - Al Katrib, Mirella; Perrin, Lara; Planes, Emilie
Abstract : Electrodeposition is investigated in this work as an alternative method to develop a large‐area perovskite active layer for solar device application. In addition to the single perovskite MAPbI3, the deposition of mixed perovskites MAPbI x Cl1− x and MA1− y FA y PbI3− x Br x is studied. This study is unique since these mixed perovskites have never been developed by electrodeposition before. It is noticed that depending on the ratios of FA, Br, and Cl infiltrated into the perovskite lattice, different microstructures and optical and chemical properties are obtained, having an impact on the photovoltaic performance of the perovskite layer. In fact, increasing the percentages of FA, Br, and Cl in the mixed perovskite improves the photovoltaic performance. Thanks to a maturation step carried out under vacuum at 40 °C for 500 h, the performances can be significantly improved, at best by 60%, to reach record efficiencies of 10%. An improvement of the stability under air at 40 °C is also observed. All the results obtained are compared with recent results in the literature, which makes it possible to appreciate the originality and innovation of the study proposed in this article. In summary, this work illustrates the importance of electrodeposition and its flexibility to develop different types of perovskites. Abstract : Electrodeposition is used for the first time for the deposition of mixed perovskite. Thanks to a maturation step, the performances can be significantly improved, to reach record efficiencies of 10%. An improvement of the stability under air at 40 °C is also observed. Electrodeposition seems to be an alternative method to develop large‐area perovskite layers for application in solar devices.